New Russian Economic Accounting for the New Economy - Tatiana L. Shcheglova (Мир новой экономики, 2018)
When discussing the relevance of transformation of the Russian accounting or the digital economy the authors usually explore Autonomous these two areas. Examination of their relationship helps to explain the modern trends in the development of both theory and practice of accounting, Examination of their relationship helps to explain the modern trends in the development of both theory and practice of accounting. This explains the novelty of the subject and the relevance of the study. The aim of the study was substantiation of author’s vision of the specific directions of reforming of accounting. The emergence in Russia of a new economic accounting and relevant of science, “integrated accounting” are made possible by modern digital technology and tools of data analysis, forecasting. Methodology or a system of knowledge about the organization of accounting activities, in addition to scientific approaches, use development trends of the economic theory of the XX century, which explain the emergence of the digital economy and the expansion of the boundaries of Accounting and Russian accounting. Results. Broad use of integrated accounting and its acceptance for a basis of information support of enterprise management necessary in order to meet the new needs of stakeholders, to increase the competitiveness of enterprises and the country in a digital economy. The distribution integrated record will contribute to overcoming the country’s backwardness in the field of accounting and will accelerate the development of the digital economy. Outlook. The development of integrated accounting will not be too expensive for capital investments but will require improvement in the field of training. the author proposes a number of specific changes in education and training in the field of integrated accounting.